Modified delivery technique using one lung ventilation for the surgical management of an intact pulmonary hydatid cyst: a case report - Bassam Osman; Bassel Hafez; Joudie Sahar Alwan; Samir Akel (Elsevier, 2023)
Hydatid disease is caused by the parasite 'Echinococcus granulosus' that infects both children and adults living in close contact with dogs and livestock. Hydatid disease remains a burden to many countries where the disease is endemic especially in the Mediterranean, South America and Australia. In children, hydatid cysts occur more commonly in the lungs rather than the liver due to permissive lung architecture facilitating rapid growth and the rise of complications. In this report, we present a case of an 8-year-old boy with a large pulmonary hydatid cyst causing nonspecific chest pain. Despite negative serological testing, decision was to proceed with surgical excision based on high clinical and radiologic suspicion. Considering the rise of VATS hydatid cyst excision, we present our approach via a birth/delivery technique using a classical posterolateral thoracotomy with an isolated single lung ventilation. Due to several challenges discussed in our paper below, the thoracotomy and sternotomy approaches remain widely used for the surgical excision of intact cysts and more remain prevalent than the thoracoscopic approach. The choice of approach remains the one that the surgeon is most comfortable with. In the discussion part of this paper, we present the recent literature about the presentation, diagnosis and management of this disease which remain challenging especially in low-income countries where the disease is endemic. This manuscript was prepared following the CARE guidelines.